Gene expression plasticity in response to salinity acclimation in threespine stickleback ecotypes from different salinity habitats. Issue 10 (13th March 2017) - Gibbons, Taylor C.; Metzger, David C. H.; Healy, Timothy M.; Schulte, Patricia M.
Abstract: Phenotypic plasticity is thought to facilitate the colonization of novel environments and shape the direction of evolution in colonizing populations. However, the relative prevalence of various predicted patterns of changes in phenotypic plasticity following colonization remains unclear. Here, we use a whole‐transcriptome approach to characterize patterns of gene expression plasticity in the gills of a freshwater‐adapted and a saltwater‐adapted ecotype of threespine stickleback ( Gasterosteus aculeatus ) exposed to a range of salinities. The response of the gill transcriptome to environmental salinity had a large shared component common to both ecotypes (2159 genes) with significant enrichment of genes involved in transmembrane ion transport and the restructuring of the gill epithelium. This transcriptional response to freshwater acclimation is induced at salinities below two parts per thousand. There was also differentiation in gene expression patterns between ecotypes (2515 genes), particularly in processes important for changes in the gill structure and permeability. Only 508 genes that differed between ecotypes also responded to salinity and no specific processes were enriched among this gene set, and an even smaller number (87 genes) showed evidence of changes in the extent of the response to salinity acclimation between ecotypes. No pattern of relative expression dominated among these genes, suggesting that neither gains nor losses of plasticity dominated the changes in expression patterns between the ecotypes. These data demonstrate that multiple patterns of changes in gene expression plasticity can occur following colonization of novel habitats.